02.35 Time of flight mass cytometry (cytof) and rna sequencing interrogation of 'pathogenic' gm-csf lymphocytes in human spondyloarthritis. (1st March 2017) - Al-Mossawi, Hussein; Ridley, Anna; Wit, Jelle de; Hammitzsch, Ariane; Chen, Liye; Bowness, Paul
Abstract : Background: Immunological, genetic and therapeutic studies have implicated T lymphocytes in the pathogenesis of Spondyloarthritis (SpA). GM-CSF is emerging as a cytokine that marks out pathogenic T lymphocytes. Inhibition of this cytokine pathway in the SKG mouse model of SpA leads to improvement of joint scores. Methods: Matched blood (PBMC) and synovial fluid (SFMC) from patients with SpA was studied ex-vivo using a 40 colour surface and intracellular CyTOF panel. CyTOF findings were validated by flow cytometry in a cohort of patients with SpA, rheumatoid arthritis (RA) controls and healthy donors. CyTOF data was analysed by multi-dimensional viSNE mapping in order to understand the heterogeneity of the synovial fluid inflammatory response. Novel triple cytokine capture was used to purify GM-CSF producing lymphocytes to high purity and RNA sequencing used to interrogate their transcriptional profile. Results: CyTOF revealed ex-vivo GM-CSF production from multiple lymphoid cell lineages, with CD4 and CD8 cells the main producers in PBMC and SFMC. GM-CSF production overlaps with multiple other cytokines including IL-17A, IFN- and TNF-. 43% (SEM 3.98) of all GM-CSF producing cells in SpA PBMC were CD4 cells. The percentage of CD4 cells producing GM-CSF was significantly increased in SpA PBMC ex-vivo compared to healthy controls (mean 7.73% vs 4.96% n=38, p<0.005). The mean percentage of GM-CSF-positive CD4 cells from ex-vivo SFMCs was 32.2%, and was significantly higher compared to matched PBMC (n=5, p=0.005). RNA sequencing of capture-sorted GM-CSF-positive human CD4 cells showed a unique transcriptional profile and validated key genes previously shown to drive pathogenicity in mouse models of type-17 immune-mediated disease. Conclusions: The synovial fluid of patients with SpA shows an expanded GM-CSF signature. This corresponds with an expansion of GM-CSF producing T lymphocytes in the peripheral blood of patients with SpA compared to controls. Human GM-CSF-positive CD4 cells have a unique 'pathogenic' transcriptional profile.